2018
DOI: 10.1002/jcp.27776
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in leukemia: Tumor suppressors and oncogenes with prognostic potential

Abstract: Leukemia is known as a progressive malignant disease, which destroys the blood‐forming organs and results in adverse effects on the proliferation and development of leukocytes and their precursors in the blood and bone marrow. There are four main classes of leukemia including acute leukemia, chronic leukemia, myelogenous leukemia, and lymphocytic leukemia. Given that a variety of internal and external factors could be associated with the initiation and progression of different types of leukemia. One of the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 216 publications
1
50
0
1
Order By: Relevance
“…8 The meta-analysis of Rashed et al 52 pointed out that miR-24 could be used as a diagnostic discriminatory biomarker between ALL and AML as it is expressed at lower levels in ALL compared to AML. Our results refer to a significant increase in miR- 24 and Zhang et al 37 reported a low expression of miR-24 with newly diagnosed childhood ALL. It was reported that overexpression of miR-24 promotes myelopoiesis and inhibits B lymphopoiesis in haematopoietic progenitors 17,54 and during adult blood development.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…8 The meta-analysis of Rashed et al 52 pointed out that miR-24 could be used as a diagnostic discriminatory biomarker between ALL and AML as it is expressed at lower levels in ALL compared to AML. Our results refer to a significant increase in miR- 24 and Zhang et al 37 reported a low expression of miR-24 with newly diagnosed childhood ALL. It was reported that overexpression of miR-24 promotes myelopoiesis and inhibits B lymphopoiesis in haematopoietic progenitors 17,54 and during adult blood development.…”
Section: Discussionsupporting
confidence: 82%
“…By promoting proliferation, invasion and inhibiting apoptosis, miR‐21 is considered as a common oncomiR that modulates the expression of multiple cancer‐related target genes 22,23 . Aberrant expression of oncomiRs (miR‐21) was reported to promote leukaemogenesis through elevating the leukaemic stem/progenitor cell population, promoting cell proliferation, blocking cell differentiation, and lessening cell apoptosis 24 . In our study, we recorded a significant increase in miR‐21 expression level in paediatric ALL patients especially B‐cell lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the relationship between miRNAs and tumors is becoming a hotspot of current research . If the target gene of the miRNA is an oncogene, and the expression of miRNA is below normal level, it will lead to the increase of protein encoded by the oncogene and thus promotes the occurrence of tumors . In contrast, if the target gene of the miRNA is a tumor suppressor, and the expression of miRNA is higher than normal level, it will lead to the decrease of the tumor suppressor and also induces the occurrence of tumors .…”
Section: Introductionmentioning
confidence: 99%
“…If the target gene of the miRNA is an oncogene, and the expression of miRNA is below normal level, it will lead to the increase of protein encoded by the oncogene and thus promotes the occurrence of tumors . In contrast, if the target gene of the miRNA is a tumor suppressor, and the expression of miRNA is higher than normal level, it will lead to the decrease of the tumor suppressor and also induces the occurrence of tumors . Because one miRNA can regulate the expression of many oncogenes or tumor suppressor genes, using miRNA as a therapeutic target may be more effective than using a single oncogene or tumor suppressor gene as a therapeutic target .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that microRNA-155 is abnormally expressed in various tumors and plays a centrol role in the process of tumor initiation, progression, invasion, and metastasis [29][30][31][32][33][34][35] . Our results indicated that expression of microRNA-155 can be up-regulated in some patients of gastric cancer and down-regulated in others.…”
Section: Discussionmentioning
confidence: 99%